2021
DOI: 10.3390/nu14010164
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Addictive Eating and Dietary Intake: A Systematic Review

Abstract: (1) Background: Research suggests that certain foods may have addictive effects; however, no reviews have systematically appraised studies in this area. The aims of this review were to determine the nutrients, foods and dietary patterns associated with addictive eating. (2) Methods: Published studies up to November 2020 were identified through searches of 6 electronic databases. Eligible studies included those in in children and adults that reported dietary intakes of individuals with ‘food addiction’. (3) Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
(213 reference statements)
0
14
0
Order By: Relevance
“…In a 2014 systematic review of FA prevalence, the weighted mean number of symptoms for adults ( n = 8 studies) was 2.8 (range from 1.8 to 4.6) out of a possible score of seven, with females reporting higher number of symptoms compared to males [ 49 ]. Additionally, more recent reviews of FA within adult populations using the updated YFAS 2.0 report that the total number of symptoms are often in the severe form (≥6 symptoms out of a possible 11) [ 15 , 34 , 50 , 51 ]. This contrast between the two age groups may indicate a progression in severity as an individual transitions from adolescence to adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2014 systematic review of FA prevalence, the weighted mean number of symptoms for adults ( n = 8 studies) was 2.8 (range from 1.8 to 4.6) out of a possible score of seven, with females reporting higher number of symptoms compared to males [ 49 ]. Additionally, more recent reviews of FA within adult populations using the updated YFAS 2.0 report that the total number of symptoms are often in the severe form (≥6 symptoms out of a possible 11) [ 15 , 34 , 50 , 51 ]. This contrast between the two age groups may indicate a progression in severity as an individual transitions from adolescence to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is not a universally accepted definition of what FA is, however the term generally refers to the excessive and uncontrolled consumption of highly palatable foods within an addictive-like pattern of eating, commonly operationalised through the Yale Food Addiction Scale (YFAS) [ 4 ]. It has been suggested that highly palatable and ultra-processed foods in combination with individual differences and environmental influences may uniquely activate the reward system of the brain, triggering and reinforcing eating behaviours such as addictive eating or FA in susceptible individuals [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In animal model studies, rats have been observed to exhibit behaviors associated with addiction when given intermittent access to sugar, but not with ad libitumaccess [ 56 ]. The results of human studies are not consistent, making it significantly more difficult to verify the concept of food (and sugar) addiction [ 57 , 58 ]. It is important to emphasize that the term “food addiction” is not currently classified as a mental disorder in the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) [ 59 ].…”
Section: Sweet Taste Perceptionmentioning
confidence: 99%
“…Identifying individual trigger foods that should be avoided can be helpful. Usually, these foods are a combination of high fat and refined carbohydrates [ 12 ]. Foods to avoid can be modified throughout the treatment and recovery process using trial-and-error as well as exposure-based therapies.…”
Section: Clinical Considerations Of Ultra-processed Food Addiction Ac...mentioning
confidence: 99%
“…There is growing trend toward use of the term “ultra-processed food addiction” (UPFA) emphasizing noteworthy differences from minimally processed foods in their addictive potential [ 8 12 ]. Given that the YFAS specifically asks about the consumption of ultra-processed foods with added sugars, salts, and fats, the terms FA and UPFA have been used interchangeably.…”
Section: Introductionmentioning
confidence: 99%